Habilitation, health, and agency : a framework for basic justice - Becker, Lawrence C. (Oxford University Press, 2012)
Lawrence C. Becker introduces an unconventional set of background ideas for future philosophical work on normative theories of basic justice. The organizing concept is habilitation - the process of equipping a person or thing with functional abilities or capacities.